PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP HASIL PENGEMBANGAN SUMBER DAYA MANUSIA MAJELIS PENDIDIKAN DASAR DAN MENENGAH MUHAMMADIYAH CABANG TANJUNG SARI - Kemal, Isthifa; Rusmiati, Rusmiati (Universitas Indraprasta PGRI, 2024)
This study aims to examine the influence of leadership and work discipline of the Dikdasmen assembly on the Development of Human Resources (HR) of the Dikdasmen Tanjung Sari Branch. This study uses a quantitative research method, namely field research using scientific studies by expert scientists. The population in this study amounted to 150 people, with a sample of 60 people. Data was obtained through random questionnaires given to respondents as many as three types of questionnaires, namely leadership questionnaires, work discipline and HR development. Data analysis used the t-test and simple regression for the first and second hypotheses, while for the third hypothesis using the Simultaneous F Test and Simple Multiple Linear Regression Test. The first hypothesis obtained t count 7.114 while for t table 1.67 at a significance level of 0.05 because t count > t table then reject H10 and accept H1a. with a regression equation Y = 44.312 + 0.657X and a Regression value of 0.413. The second hypothesis obtained a count of 6.621 while for ttable 1.67 at a significant level of 0.05 because tcount > ttable then reject H20 and accept H2a. with the regression equation Y = 41.970 + 0.423X and a Regression value of 0.353. The third hypothesis obtained Fcount 28.94 and Ftable at a Significance level of 0.05 of 3.16 because Fcount > from Ftable then H0 is rejected and Ha is accepted. The resulting regression equation is 88.2408 + 0.3800X1 + 0.5718X2 and the value of the Regression is 0.515. This study concludes that there is an influence of Leadership on HR development, there is an influence of Work Discipline on HR development and There is a simultaneous influence between leadership and work discipline on HR development at Dikdasmen Tanjung Sari Branch.